2021
DOI: 10.1186/s13089-021-00217-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of lung ultrasound for SARS-CoV-2: a retrospective cohort study

Abstract: Background As medical infrastructures are strained by SARS-CoV-2, rapid and accurate screening tools are essential. In portions of the world, reverse transcription polymerase chain reaction (RT-PCR) testing remains slow and in limited supply, and computed tomography is expensive, inefficient, and involves exposure to ionizing radiation. Multiple studies evaluating the efficiency of lung point-of-care ultrasound (POCUS) have been published recently, but include relatively small cohorts and often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…The US imaging can be performed daily for patients having severe infection of the lungs due to COVID-19 for better management [16], [17]. The recent work [18] utilizes POCUS for diagnosis of COVID-19 and was found to be very effective for rapid screening as well as diagnosis of COVID-19 in symptomatic patients. It was also concluded that lung POCUS was not very accurate for patients having a history of heart failure, severe emphysema, and interstitial lung disease [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The US imaging can be performed daily for patients having severe infection of the lungs due to COVID-19 for better management [16], [17]. The recent work [18] utilizes POCUS for diagnosis of COVID-19 and was found to be very effective for rapid screening as well as diagnosis of COVID-19 in symptomatic patients. It was also concluded that lung POCUS was not very accurate for patients having a history of heart failure, severe emphysema, and interstitial lung disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…The recent work [18] utilizes POCUS for diagnosis of COVID-19 and was found to be very effective for rapid screening as well as diagnosis of COVID-19 in symptomatic patients. It was also concluded that lung POCUS was not very accurate for patients having a history of heart failure, severe emphysema, and interstitial lung disease [18]. The availability and use of POCUS screening helped in the identification of symptomatic patients having COVID-19 and does not require performing the RT-PCR test in the resource-constrained settings and during peak periods of a surge in COVID-19 [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly those who tested positive on RT-PCR had higher scores (optimal cut-off scores are shown in Table 1). (25,26). It was also demonstrated that complete (12-zone) studies were 5% more sensitive and 4% more specific than less thorough studies.…”
Section: Summary Of Results An Overview Of the Characteristics Of All The Included Studies Ismentioning
confidence: 96%
“…Brenner et al, showed that when only complete 12-zone studies were included in their analysis, both sensitivity and specificity of LUS were improved. (26) The heterogenous criteria used to determine whether a positive LUS may also have affected the results of the various. Various thresholds were used for ruling in this diagnosis, ranging from any B lines to a minimum number of affected zones to a minimum severity score.…”
Section: Discussionmentioning
confidence: 99%